Preparation method and application of defective aluminum-based metal organic framework material
By reacting a solution containing aluminum salt and 3,5-pyrazole dicarboxylic acid with sodium hydroxide at room temperature, defective aluminum-based metal organic framework materials were prepared, and the poor water absorption performance under low humidity in the prior art was solved and The environmental problems of the heat treatment method achieve efficient water absorption and low-cost water collection effects.
Patent Information
- Application Number
- CN202411493600.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The actual application performance of existing metal organic framework materials in all day water adsorbents under low relative humidity is poor, and the existing methods of heat treatment to prepare defective MOFs materials require high temperature and the use of toxic solvents, which affects environmental protection.
By mixing a solution containing aluminum salt and 3,5-pyrazole dicarboxylic acid with sodium hydroxide at room temperature, controlling the reaction temperature and time, a defective aluminum-based metal organic framework material has high water absorption performance and good heat stability.
It achieves efficient water absorption at extremely low humidity, reduces energy costs, and avoids the use of toxic solvents, improves the yield and stability of the material, and is suitable for water collection in arid areas.
Smart Images

Figure CN119161592A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the research field of metal organic framework materials, and in particular to a preparation method and application of a defective aluminum-based metal organic framework material. Background Art
[0002] Personal health and quality of life depend largely on access to clean water in daily life. More than half of the world's population lives in water-scarce conditions, and freshwater supply is insufficient to meet demand. To alleviate this problem, research over the past few decades has focused on harvesting fresh water through methods such as rainwater harvesting, fog capture, dew harvesting, and steam condensation, as well as treating contaminated water through harmless treatment. Considering the widespread presence of vapor in the atmosphere, porous hygroscopic adsorbents are being studied to harvest water from the air. Adsorption-assisted atmospheric water harvesting (SAWH) materials, such as hygroscopic polymers, hygroscopic salts, and metal-organic frameworks (MOFs), have been developed. Currently, water harvesting technology based on SAWH has been developed, but the practical application performance of water adsorbents throughout the day at low relative humidity is not satisfactory. How to achieve high water absorption capacity at low relative humidity remains a huge challenge.
[0003] MOFs have a high specific surface area and large porosity, and the size, shape, and hydrophilicity of their pores can be adjusted to a certain extent. Their unique designability allows for the optimization of their water adsorption properties through human intervention. Therefore, MOFs have broad application prospects in air-water harvesting, particularly in areas with extremely low humidity.
[0004] In recent years, the introduction of defects into MOFs has garnered significant attention. Vacancies at metal centers, missing organic ligands, or the addition of defective or functionalized ligands can all lead to crystal defects in MOFs—regions where the original periodic structure of the framework is disrupted. In some cases, defects can enhance the water absorption properties of MOFs by altering their surface properties, internal pore structure, or creating new active metal sites. However, these strategies can alter the crystal structure and reduce its stability.
[0005] On the other hand, defects in MOFs can also be manipulated through thermal treatment. By adjusting the reaction temperature and time, defects can be introduced into the MOFs to improve their water absorption at extremely low humidity levels, while also maintaining good thermal stability. Existing thermal treatment methods require temperatures above 200°C, which are high and require specific conditions to achieve. Alternatively, defects can be created by adding acids or other solvents at around 80°C. These acids and other solvents are often toxic and can easily pollute the environment, which is not environmentally friendly. Summary of the Invention
[0006] In order to overcome the problem of poor structural stability of MOFs with crystal defects and the shortcomings of existing heat treatment in preparing defective MOFs materials, the present invention provides a preparation method and application of a defective aluminum-based metal organic framework material.
[0007] A method for preparing a defective aluminum-based metal-organic framework material is as follows:
[0008] (1) mixing a first solution containing aluminum salt and a second solution containing 3,5-pyrazoledicarboxylic acid at room temperature and pressure, then adding solid sodium hydroxide and stirring until completely dissolved to obtain a mixed solution;
[0009] The concentration range of the first solution is 0.005 g / mL to 0.015 g / mL, the concentration range of the second solution is 0.004 g / mL to 0.010 g / mL, and the ratio of the added amount of sodium hydroxide solid to the mass of the aluminum salt is 0.3:1 to 1.1.
[0010] The solvent is water; the aluminum salt is selected from one or more of aluminum chloride hexahydrate, anhydrous aluminum sulfate, anhydrous aluminum nitrate and potassium aluminum sulfate dodecahydrate, and the preferred aluminum salt is aluminum chloride hexahydrate.
[0011] (2) reacting the mixed solution at a certain temperature for a certain time, and after the reaction is completed, naturally cooling the product to room temperature to obtain a precipitate.
[0012] The reaction temperature is 60-120°C and the reaction time is 12-48 hours. Preferably, the reaction temperature is 100°C and the reaction time is 12 hours; the reaction temperature is 120°C and the reaction time is 24 hours; the reaction temperature is 60°C and the reaction time is 48 hours.
[0013] (3) The obtained precipitate is centrifuged and dried, and weighed to obtain a defective aluminum-based metal-organic framework material.
[0014] The yield of the defective aluminum-based metal organic framework material prepared by the method is above 50%.
[0015] The structure of the prepared defective aluminum-based metal-organic framework material crystals is rough and there are a large number of defects on the surface.
[0016] The specific process of applying the above-mentioned defective aluminum-based metal-organic framework material to water collection in extremely low humidity environments is as follows:
[0017] The defective aluminum-based metal-organic framework material was placed in an environment with an ambient humidity of 10-15%, and the material absorbed moisture from the air until equilibrium was reached.
[0018] The advantages and positive effects of the present invention are:
[0019] 1. The preparation method of the defective aluminum-based metal-organic framework material provided by the present invention has a simple preparation process, mild reaction conditions, low cost and high yield.
[0020] 2. The defective aluminum-based metal-organic framework material prepared by the present invention has uniform size, good stability, and better water absorption effect under extremely low humidity, and can be used as an ideal adsorption material in extremely arid areas.
[0021] 3. The defective aluminum-based metal-organic framework material prepared by the present invention can reduce the energy cost used.
[0022] 4. The defective aluminum-based metal-organic framework material prepared by the present invention has broad potential application value and can be used for water extraction in arid areas. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 10 are infrared spectra of Example 6, Example 8, and Example 10 of the present invention;
[0024] Figure 2 Surface morphology diagrams of Examples 6, 8 and 10 of the present invention; wherein, Figure 2 a is Example 6, Figure 2 b is Example 8, Figure 2 c is Example 10;
[0025] Figure 3 is a thermogravimetric analysis diagram of Example 6, Example 8 and Example 10 of the present invention;
[0026] Figure 4 are differential scanning calorimetry graphs of Examples 6, 8, and 10 of the present invention;
[0027] Figure 5 1 is a water absorption curve diagram of the comparative example, Example 6, Example 8 and Example 10 of the present invention under extremely low humidity (12.5%);
[0028] Figure 6 Graph showing the water absorption capacity of the comparative example, Example 6, Example 8 and Example 10 of the present invention under extremely low humidity (12.5%). DETAILED DESCRIPTION
[0029] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0030] This invention discloses the preparation and application of a defective metal-organic framework (MOF) material. Using aluminum chloride hexahydrate and 3,5-pyrazoledicarboxylic acid as the primary raw materials, the method constructs a defective MOF material by adjusting the reaction temperature and time to achieve high water absorption. The defective Al-MOF has a rough surface structure, resulting in efficient water absorption at low humidity. Furthermore, this strategy is simple to operate, requires mild reaction conditions, and is easily synthesized on a large scale. This strategy provides insights into the design and synthesis of novel aluminum-based MOF materials, facilitating their industrial application.
[0031] Example 1
[0032] (1) Weigh 0.45 g of 3,5-pyrazoledicarboxylic acid and 0.7 g of aluminum chloride hexahydrate, dissolve them in 50 ml of deionized water, mix the two solutions, and then add 0.2 g of sodium hydroxide solid and stir until completely dissolved to obtain a mixed solution.
[0033] (2) The homogeneous solution formed above was placed in a 200 ml hydrothermal reactor and heated to 100° C., and reacted under this condition for 48 hours.
[0034] (3) After the growth is completed, the product is naturally cooled to room temperature to obtain a precipitate, and the obtained precipitate is centrifuged and dried, and weighed to obtain an aluminum-based metal organic framework material. The yield is measured. As shown in Table 1, the yield of the sample is 67.5%.
[0035] (4) Weigh 0.2 g of the sample and place it in a constant temperature and humidity chamber at a humidity of 40%. After 1-2 hours, take out the water-absorbing sample and measure its water absorption. As shown in Table 1, the water absorption of the sample at 40% humidity and 25°C is 0.385 g / g.
[0036] Example 2
[0037] (1) Weigh 0.45 g of 3,5-pyrazoledicarboxylic acid and 0.7 g of aluminum chloride hexahydrate, dissolve them in 50 ml of deionized water, mix the two solutions, and then add 0.2 g of sodium hydroxide solid and stir until completely dissolved to obtain a mixed solution.
[0038] (2) The homogeneous solution formed above was placed in a 200 ml hydrothermal reactor and heated to 100° C., and reacted under this condition for 24 h.
[0039] (3) After the growth is completed, the product is naturally cooled to room temperature to obtain a precipitate, and the obtained precipitate is centrifuged and dried, and weighed to obtain a defective aluminum-based metal-organic framework material. The yield is measured. As shown in Table 1, the yield of the sample is 77.3%.
[0040] (4) Weigh 0.2 g of the sample and place it in a constant temperature and humidity chamber at a humidity of 40%. After 1-2 hours, take out the water-absorbing sample and measure its water absorption. As shown in Table 1, the water absorption of the sample at 40% humidity and 25°C is 0.312 g / g.
[0041] Example 3
[0042] (1) Weigh 0.45 g of 3,5-pyrazoledicarboxylic acid and 0.7 g of aluminum chloride hexahydrate, dissolve them in 50 ml of deionized water, mix the two solutions, and then add 0.2 g of sodium hydroxide solid and stir until completely dissolved to obtain a mixed solution.
[0043] (2) The homogeneous solution formed above was placed in a 200 ml hydrothermal reactor and heated to 80°C. The reaction was carried out under this condition for 12 hours.
[0044] (3) After the growth is completed, the product is naturally cooled to room temperature to obtain a precipitate, and the obtained precipitate is centrifuged and dried, and weighed to obtain a defective aluminum-based metal-organic framework material. The yield is measured. As shown in Table 1, the yield of the sample is 60.1%.
[0045] (4) Weigh 0.2 g of the sample and place it in a constant temperature and humidity chamber at a humidity of 40%. After 1-2 hours, take out the water-absorbing sample and measure its water absorption. As shown in Table 1, the water absorption of the sample at 40% humidity and 25°C is 0.367 g / g.
[0046] Example 4
[0047] (1) Weigh 0.45 g of 3,5-pyrazoledicarboxylic acid and 0.7 g of aluminum chloride hexahydrate, dissolve them in 50 ml of deionized water, mix the two solutions, and then add 0.2 g of sodium hydroxide solid and stir until completely dissolved to obtain a mixed solution.
[0048] (2) The homogeneous solution formed above was placed in a 200 ml hydrothermal reactor and heated to 80°C. The reaction was carried out under this condition for 24 hours.
[0049] (3) After the growth is completed, the product is naturally cooled to room temperature to obtain a precipitate, and the obtained precipitate is centrifuged and dried, and weighed to obtain a defective aluminum-based metal-organic framework material. The yield is measured. As shown in Table 1, the yield of the sample is 66.4%.
[0050] (4) Weigh 0.2 g of the sample and place it in a constant temperature and humidity chamber at a humidity of 40%. After 1-2 hours, take out the water-absorbing sample and measure its water absorption. As shown in Table 1, the water absorption of the sample at 40% humidity and 25°C is 0.268 g / g.
[0051] Example 5
[0052] (1) Weigh 0.45 g of 3,5-pyrazoledicarboxylic acid and 0.7 g of aluminum chloride hexahydrate, dissolve them in 50 ml of deionized water, mix the two solutions, and then add 0.2 g of sodium hydroxide solid and stir until completely dissolved to obtain a mixed solution.
[0053] (2) The homogeneous solution formed above was placed in a 200 ml hydrothermal reactor and heated to 120° C., and reacted under this condition for 12 h.
[0054] (3) After the growth is completed, the product is naturally cooled to room temperature to obtain a precipitate, and the obtained precipitate is centrifuged and dried, and weighed to obtain a defective aluminum-based metal-organic framework material. The yield is measured. As shown in Table 1, the yield of the sample is 55.4%.
[0055] (4) Weigh 0.2 g of the sample and place it in a constant temperature and humidity chamber at a humidity of 40%. After 1-2 hours, take out the water-absorbing sample and measure its water absorption. As shown in Table 1, the water absorption of the sample at 40% humidity and 25°C is 0.21 g / g.
[0056] Example 6
[0057] (1) Weigh 0.45 g of 3,5-pyrazoledicarboxylic acid and 0.7 g of aluminum chloride hexahydrate, dissolve them in 50 ml of deionized water, mix the two solutions, and then add 0.2 g of sodium hydroxide solid and stir until completely dissolved to obtain a mixed solution.
[0058] (2) The homogeneous solution formed above was placed in a 200 ml hydrothermal reactor and heated to 120° C., and reacted under this condition for 24 h.
[0059] (3) After the growth is completed, the product is naturally cooled to room temperature to obtain a precipitate, and the obtained precipitate is centrifuged and dried, and weighed to obtain a defective aluminum-based metal-organic framework material. The yield is measured. As shown in Table 1, the yield of the sample is 60.7%.
[0060] (4) Weigh 0.2 g of the sample and place it in a constant temperature and humidity chamber at a humidity of 40%. After 1-2 hours, take out the water-absorbing sample and measure its water absorption. As shown in Table 1, the water absorption of the sample at 40% humidity and 25°C is 0.468 g / g.
[0061] The solid sample obtained in this example was detected by infrared spectrometer, and the following Figure 1 As shown in the infrared spectrum, it can be seen from the infrared spectrum that MOF-303 has a -1 、1480cm -1 and 1535cm -1The characteristic peaks correspond to the stretching vibrations of N-NH, CC and CN, respectively, proving the successful preparation of the defective aluminum-based metal-organic framework material.
[0062] like Figure 2 As shown in a, the surface structure of the prepared sample is relatively smooth with few defects. Figure 3 He Ru Figure 4 Thermogravimetric analysis (TGA) of the prepared sample is shown in Figure 2. The 10.2% weight loss of MOF-303 at 325°C is attributed to the evaporation of water molecules and the decomposition of the non-coordinating H2PZDC. MOF-303 begins to decompose at 472.2°C. At around 600°C, MOF-303 is oxidized to aluminum oxide, resulting in a 35% mass loss. These results demonstrate the excellent stability of the prepared sample.
[0063] Example 7
[0064] (1) Weigh 0.45 g of 3,5-pyrazoledicarboxylic acid and 0.7 g of aluminum chloride hexahydrate, dissolve them in 50 ml of deionized water, mix the two solutions, and then add 0.2 g of sodium hydroxide solid and stir until completely dissolved to obtain a mixed solution.
[0065] (2) The homogeneous solution formed above was placed in a 200 ml hydrothermal reactor and heated to 120° C., and reacted under this condition for 48 hours.
[0066] (3) After the growth is completed, the product is naturally cooled to room temperature to obtain a precipitate, and the obtained precipitate is centrifuged and dried, and weighed to obtain a defective aluminum-based metal-organic framework material. The yield is measured. As shown in Table 1, the yield of the sample is, As shown in Table 1, the yield of the sample is 64.5%.
[0067] (4) Weigh 0.2 g of the sample and place it in a constant temperature and humidity chamber at a humidity of 40%. After 1-2 hours, take out the water-absorbing sample and measure its water absorption. As shown in Table 1, the water absorption of the sample at 40% humidity and 25°C is 0.20 g / g.
[0068] Example 8
[0069] (1) Weigh 0.45 g of 3,5-pyrazoledicarboxylic acid and 0.7 g of aluminum chloride hexahydrate, dissolve them in 50 ml of deionized water, mix the two solutions, and then add 0.2 g of sodium hydroxide solid and stir until completely dissolved to obtain a mixed solution.
[0070] (2) The homogeneous solution formed above was placed in a 200 ml hydrothermal reactor and heated to 100° C., and reacted under this condition for 12 h.
[0071] (3) After the growth is completed, the product is naturally cooled to room temperature to obtain a precipitate, and the obtained precipitate is centrifuged and dried, and weighed to obtain a defective aluminum-based metal-organic framework material. The yield is measured. As shown in Table 1, the yield of the sample is 53.8%.
[0072] (4) Weigh 0.2 g of the sample and place it in a constant temperature and humidity chamber at a humidity of 40%. After 1-2 hours, take out the water-absorbing sample and measure its water absorption. As shown in Table 1, the water absorption of the sample at 40% humidity and 25°C is 0.57 g / g.
[0073] The obtained solid sample was detected by infrared spectrometer and the following Figure 1 As shown in the infrared spectrum, it can be seen from the infrared spectrum that MOF-303 has a -1 、1482cm -1 and 1536cm -1 The characteristic peaks correspond to the stretching vibrations of N-NH, CC and CN, respectively, proving the successful preparation of the defective aluminum-based metal-organic framework material.
[0074] like Figure 2 As shown in b, the surface structure of the prepared sample is rough and has many defects. Figure 3 He Ru Figure 4 Thermogravimetric analysis (TGA) of the prepared sample is shown in Figure 2. The 16% weight loss of MOF-303 at 323°C is attributed to the evaporation of water molecules and the decomposition of the non-coordinating H2PZDC. MOF-303 begins to decompose at 468.5°C. At around 600°C, MOF-303 is oxidized to aluminum oxide, resulting in a mass loss of 25.8%. These results demonstrate the excellent stability of the prepared sample.
[0075] Example 9
[0076] (1) Weigh 0.45 g of 3,5-pyrazoledicarboxylic acid and 0.7 g of aluminum chloride hexahydrate, dissolve them in 50 ml of deionized water, mix the two solutions, and then add 0.2 g of sodium hydroxide solid and stir until completely dissolved to obtain a mixed solution.
[0077] (2) The homogeneous solution formed above was placed in a 200 ml hydrothermal reactor and heated to 80° C., and reacted under this condition for 48 hours.
[0078] (3) After the growth is completed, the product is naturally cooled to room temperature to obtain a precipitate, and the obtained precipitate is centrifuged and dried, and weighed to obtain a defective aluminum-based metal-organic framework material. The yield is measured. As shown in Table 1, the yield of the sample is 67.1%.
[0079] (4) Weigh 0.2 g of the sample and place it in a constant temperature and humidity chamber at a humidity of 40%. After 1-2 hours, take out the water-absorbing sample and measure its water absorption. As shown in Table 1, the water absorption of the sample at 40% humidity and 25°C is 0.262 g / g.
[0080] Example 10
[0081] (1) Weigh 0.45 g of 3,5-pyrazoledicarboxylic acid and 0.7 g of aluminum chloride hexahydrate, dissolve them in 50 ml of deionized water, mix the two solutions, and then add 0.2 g of sodium hydroxide solid and stir until completely dissolved to obtain a mixed solution.
[0082] (2) The homogeneous solution formed above was placed in a 200 ml hydrothermal reactor and heated to 60° C., and reacted under this condition for 48 h.
[0083] (3) After the growth is completed, the product is naturally cooled to room temperature to obtain a precipitate, and the obtained precipitate is centrifuged and dried, and weighed to obtain a defective aluminum-based metal-organic framework material. The yield is measured. As shown in Table 1, the yield of the sample is 67.2%.
[0084] (4) Weigh 0.2 g of the sample and place it in a constant temperature and humidity chamber at a humidity of 40%. After 1-2 hours, take out the water-absorbing sample and measure its water absorption. As shown in Table 1, the water absorption of the sample at 40% humidity and 25°C is 0.434 g / g.
[0085] The obtained solid sample was detected by infrared spectrometer and the following Figure 1 As shown in the infrared spectrum, it can be seen from the infrared spectrum that MOF-303 has a peak at 1008 cm -1 、1485cm -1 and 1545cm -1 The characteristic peaks correspond to the stretching vibrations of N-NH, CC and CN, respectively, proving the successful preparation of the defective aluminum-based metal-organic framework material.
[0086] like Figure 2 As shown in c, the surface structure of the prepared sample is relatively rough and has many defects. Figure 3 He Ru Figure 4 Thermogravimetric analysis (TGA) of the prepared sample is shown in Figure 2. The 16% weight loss of MOF-303 at 323°C is attributed to the evaporation of water molecules and the decomposition of the non-coordinating H2PZDC. MOF-303 begins to decompose at 466.9°C. At around 600°C, MOF-303 is oxidized to aluminum oxide, resulting in a mass loss of 34.70%. These results demonstrate the excellent stability of the prepared sample.
[0087] Example 11
[0088] (1) Weigh 0.45 g of 3,5-pyrazoledicarboxylic acid and 0.7 g of aluminum chloride hexahydrate, dissolve them in 50 ml of deionized water, mix the two solutions, and then add 0.2 g of sodium hydroxide solid and stir until completely dissolved to obtain a mixed solution.
[0089] (2) The homogeneous solution formed above was placed in a 200 ml hydrothermal reactor and heated to 60° C., and reacted under this condition for 24 h.
[0090] (3) After the growth is completed, the product is naturally cooled to room temperature to obtain a precipitate, and the obtained precipitate is centrifuged and dried, and weighed to obtain a defective aluminum-based metal-organic framework material. The yield is measured. As shown in Table 1, the yield of the sample is 50.9%.
[0091] (4) Weigh 0.2 g of the sample and place it in a constant temperature and humidity chamber at a humidity of 40%. After 1-2 hours, take out the water-absorbing sample and measure its water absorption. As shown in Table 1, the water absorption of the sample at 40% humidity and 25°C is 0.22 g / g.
[0092] Example 12
[0093] (1) Weigh 0.45 g of 3,5-pyrazoledicarboxylic acid and 0.7 g of aluminum chloride hexahydrate, dissolve them in 50 ml of deionized water, mix the two solutions, and then add 0.2 g of sodium hydroxide solid and stir until completely dissolved to obtain a mixed solution.
[0094] (2) The homogeneous solution formed above was placed in a 200 ml hydrothermal reactor and heated to 60°C. The reaction was carried out under this condition for 12 hours.
[0095] (3) After the growth is completed, the product is naturally cooled to room temperature to obtain a precipitate, and the obtained precipitate is centrifuged and dried, and weighed to obtain a defective aluminum-based metal-organic framework material. The yield is measured. As shown in Table 1, the yield of the sample is 51.0%.
[0096] (4) Weigh 0.2 g of the sample and place it in a constant temperature and humidity chamber at a humidity of 40%. After 1-2 hours, take out the water-absorbing sample and measure its water absorption. As shown in Table 1, the water absorption of the sample at 40% humidity and 25°C is 0.29 g / g.
[0097] Table 1 Reaction temperature, reaction time, yield and water absorption effect of products of Examples 1-12 at 25°C-40RH%
[0098]
[0099] As shown in Table 1, the defective aluminum-based metal organic framework materials prepared in Examples 6, 8 and 10 have the largest water absorption capacity. Pure MOFs materials were used as comparative examples, and water absorption experiments were conducted in an extremely low humidity environment with the samples prepared in Examples 6, 8 and 10. Specifically,
[0100] Samples of equal mass were taken from each of the four groups of materials and placed in an environment with a temperature of 25°C and a humidity of 12.5% for a sufficient period of time until each sample was saturated with water.
[0101] like Figure 5 and Figure 6 As shown, within 180 min, the water absorption of the comparative example sample was 0.04 g / g, the water absorption of the sample of Example 6 was 0.089 g / g, the water absorption of the sample of Example 8 was 0.248 g / g, and the water absorption of the sample of Example 10 was 0.115 g / g.
[0102] It can be seen from the above water absorption values that in an extremely low humidity environment, the defective aluminum-based metal-organic framework material prepared by the present invention has a significantly improved water absorption capacity compared to the existing aluminum-based metal-organic framework.
[0103] Example 13
[0104] (1) Weigh 0.2 g of 3,5-pyrazoledicarboxylic acid and 0.25 of aluminum chloride hexahydrate, dissolve them in 50 ml of deionized water, mix the two solutions, and then add 0.068 g of sodium hydroxide solid and stir until completely dissolved to obtain a mixed solution.
[0105] (2) The homogeneous solution formed above was placed in a 200 ml hydrothermal reactor and heated to 100° C., and reacted under this condition for 48 hours.
[0106] (3) After the growth is completed, the product is naturally cooled to room temperature to obtain a precipitate, and the obtained precipitate is centrifuged and dried, and weighed to obtain an aluminum-based metal organic framework material.
[0107] Example 14
[0108] (1) Weigh 0.5 g of 3,5-pyrazoledicarboxylic acid and 0.75 g of aluminum chloride hexahydrate, dissolve them in 50 ml of deionized water, mix the two solutions, and then add 0.225 g of sodium hydroxide solid and stir until completely dissolved to obtain a mixed solution.
[0109] (2) The homogeneous solution formed above was placed in a 200 ml hydrothermal reactor and heated to 100° C., and reacted under this condition for 48 hours.
[0110] (3) After the growth is completed, the product is naturally cooled to room temperature to obtain a precipitate, and the obtained precipitate is centrifuged and dried, and weighed to obtain an aluminum-based metal organic framework material.
Claims
1. A method for preparing a defective aluminum-based metal-organic framework material, characterized in that: The specific steps are as follows: (1) mixing a first solution containing aluminum salt and a second solution containing 3,5-pyrazoledicarboxylic acid at room temperature and pressure, then adding solid sodium hydroxide and stirring until completely dissolved to obtain a mixed solution; The concentration range of the first solution is 0.005 g / mL to 0.015 g / mL, the concentration range of the second solution is 0.004 g / mL to 0.010 g / mL, and the mass ratio of the added amount of sodium hydroxide solid to the aluminum salt is 0.3:1 to 1.1; (2) reacting the mixed solution at a certain temperature for a certain time, and after the reaction is completed, naturally cooling the product to room temperature to obtain a precipitate; The reaction temperature is 60-120°C; the reaction time is 12-48h; (3) The obtained precipitate is centrifuged and dried, and weighed to obtain a defective aluminum-based metal-organic framework material.
2. The method for preparing a defective aluminum-based metal-organic framework material according to claim 1, characterized in that: The aluminum salt is selected from one or more of aluminum chloride hexahydrate, anhydrous aluminum sulfate, anhydrous aluminum nitrate and aluminum potassium sulfate dodecahydrate; the solvent is water.
3. The method for preparing a defective aluminum-based metal organic framework material according to claim 1, characterized in that: Preferably, the reaction temperature is 100° C. and the reaction time is 12 hours.
4. The method for preparing a defective aluminum-based metal-organic framework material according to claim 1, characterized in that: Preferably, the reaction temperature is 120° C. and the reaction time is 24 hours.
5. The method for preparing a defective aluminum-based metal-organic framework material according to claim 1, characterized in that: Preferably, the reaction temperature is 60° C. and the reaction time is 48 hours.
6. The method for preparing a defective aluminum-based metal organic framework material according to any one of claims 1 to 5, characterized in that: The yield of the prepared defective aluminum-based metal organic framework material is above 50%.
7. A defective aluminum-based metal-organic framework material, characterized in that: The structure of the crystals was coarse, indicating the presence of numerous defects.
8. A method for applying a defective aluminum-based metal-organic framework material, characterized in that: Used for water collection in extremely low humidity environments.
9. A method for applying a defective aluminum-based metal-organic framework material, characterized in that: The defective aluminum-based metal organic framework material is placed in an environment with a humidity of 10-15% under normal temperature conditions. The material absorbs moisture from the air until equilibrium is reached within 180 minutes, and the water absorption amount is not less than 0.089 g / g.
Citation Information
Cited By
Wide-humidity-range moisture absorption aluminum-based MOF material and preparation method thereof
CN121314551A
